2003
DOI: 10.1074/jbc.m309627200
|View full text |Cite
|
Sign up to set email alerts
|

An Isolated Class II Aminoacyl-tRNA Synthetase Insertion Domain Is Functional in Amino Acid Editing

Abstract: Aminoacyl-tRNA synthetases are responsible for activating specific amino acids and transferring them onto cognate tRNA molecules. Due to the similarity in many amino acid side chains, certain synthetases misactivate non-cognate amino acids to an extent that would be detrimental to protein synthesis if left uncorrected. To ensure accurate translation of the genetic code, some synthetases therefore utilize editing mechanisms to hydrolyze non-cognate products. Previously class II Escherichia coli proline-tRNA syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
96
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 50 publications
1
96
0
Order By: Relevance
“…The absence of an editing domain in many archaeal ThrRSs and in some bacterial ProRSs suggested that their paralogs carry out trans-editing of mischarged tRNAs. Examination of the naturally occurring paralogs AlaX, ProX, ThrX , and the ProRS paralog Ybak of Haemophilus influenzae (Wong et al 2003) showed that this is the case, as these proteins efficiently and specifically hydrolyze misacylated tRNA substrates. These data suggest that the editing domains in aaRSs may have originated from similar autonomous editing modules.…”
Section: Synthetase-like Proteinsmentioning
confidence: 99%
“…The absence of an editing domain in many archaeal ThrRSs and in some bacterial ProRSs suggested that their paralogs carry out trans-editing of mischarged tRNAs. Examination of the naturally occurring paralogs AlaX, ProX, ThrX , and the ProRS paralog Ybak of Haemophilus influenzae (Wong et al 2003) showed that this is the case, as these proteins efficiently and specifically hydrolyze misacylated tRNA substrates. These data suggest that the editing domains in aaRSs may have originated from similar autonomous editing modules.…”
Section: Synthetase-like Proteinsmentioning
confidence: 99%
“…The function of aaRS paralogs is not restricted to amino acid biosynthesis. Truncated alanyl-, prolyl-, and threonyl-tRNA synthetase-like proteins were shown to possess esterase function and be capable of specific hydrolysis of misacylated tRNA in trans (11,12), a mechanism that should increase the fidelity of the translation process.…”
mentioning
confidence: 99%
“…The unique ProRS editing domain is found in at least three different structural contexts: as an insertion (INS) between motifs 2 and 3 of the aminoacylation active site of bacterial enzymes (16,25,26), as an N-terminal extension in ProRSs of lower eukaryotes (27,28), and as a free-standing editing module (25,28). A highly conserved lysine (K279 in Ec ProRS) found in most INS domain homologs is critical for posttransfer editing function (16,29).…”
mentioning
confidence: 99%